PHYTOCHEMICAL SCREENING, ANTIMICROBIAL, AND ANTIOXIDANT ACTIVITIES OF ROOT AND LEAF EXTRACTS OF LEUCAS ASPERA - K, VASUDHA; D, ARCHANA; B, MUTYALAMMA; B, KISHORI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was designed to evaluate the phytochemical screening, antimicrobial, and antioxidant activities from the roots and leaves of Leucas aspera. Methods: The phytochemical screening and Fourier transform infrared (FTIR) analysis of root and leaf extracts were studied using standard methods. The disk diffusion method was performed to analyze the antimicrobial activity of aqueous extract, methanol extract and hexane extract of root and leaf against to selected bacterial and fungal strains. Antibiotics, streptomycin and nystatin were used as standards for bacteria and fungi, respectively. The antioxidant activity of the extracts was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and scavenging of H2O2 free radicals. Results: Preliminary phytochemical screening of extracts exhibited the presence of carbohydrates, proteins, amino acids, steroids flavonoids, terpenoids, saponins, alkaloids, tannins, and phlobatannins. Leaf extracts exhibited effective antibacterial and antifungal activities compared with root extracts against all the tested bacteria and fungi. ME of the leaves exhibited highest antibacterial activity against Staphylococcus aureus (12.8±0.31 mm), followed by Bacillus subtilis (11.4±0.3 mm), Escherichia coli (9.8±0.21 mm), and Pseudomonas aeruginosa (7.3±0.29 mm). Leaf extracts of L. aspera showed effective scavenging activity compared with root extracts. ME of the leaves showed maximum scavenging activities of 38.39 and 36.85%, respectively, against DPPH and H2O2 free radicals with half maximal inhibitory concentration values of 136.17 and 142.42 μg/ml. Conclusion: Phytochemical analysis and FTIR spectrum revealed that different plant secondary metabolites particularly alkaloids, terpenoids, and flavonoids could be responsible for antimicrobial and antioxidant activities of L. aspera leaf extracts.